2014
DOI: 10.5455/cap.20130522110439
|View full text |Cite
|
Sign up to set email alerts
|

Violence in Schizophrenia

Abstract: ÖzetPek çok psikiyatrik hasta şiddet eğilimi sergilememekte ise de günümüz toplumunda ruhsal bozukluk ve şiddet biribiyle bağlantılı görülmektedir. Genel populasyon ile kıyaslandığında şiddet davranışı riski şizofrenide istatistiksel olarak anlamlı bir yükseklik göstermiştir. Şizofrenide şiddet davranı-şı riski madde kullanım eştanılılığı ile artmaktadır. Şizofreni tanılı yetişkinlerde şiddet davranışının ortaya çıkması, antisosyal kişilk bozukluğu ve şizofreninin akut psikopatolojisi ile ilişkili iki farklı y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 97 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…Obesity is one of the most important health problems, the incidence of which has risen considerably, and which increases health care costs (Anuk et al, 2017; Aygin & Açıl, 2015; Ballı, 2013; Sevinçer, Coşkun, Konuk, & Bozkurt, 2014; Yüksel, 2016). It has been reported to be the second most frequent cause of deadly but preventable diseases following smoking (Sağlam & Güven, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity is one of the most important health problems, the incidence of which has risen considerably, and which increases health care costs (Anuk et al, 2017; Aygin & Açıl, 2015; Ballı, 2013; Sevinçer, Coşkun, Konuk, & Bozkurt, 2014; Yüksel, 2016). It has been reported to be the second most frequent cause of deadly but preventable diseases following smoking (Sağlam & Güven, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been stated in the literature that people with obesity try several methods to lose weight before having surgery (Homer, Tod, Thompson, Allmark, & Goyder, 2016; Natvik, Gjengedal, Moltu, & Raheim, 2015; Owen-Smith, Donovan, & Coast, 2017; Stuart, Brizell, McVeigh, & Irvine, 2011). Some of them regain weight (Owen-Smith et al, 2017; Sevinçer et al, 2014; Stuart et al, 2011) and consider surgical methods as the last chance to get rid of obesity (Homer et al, 2016; Natvık et al, 2015). The intended success rates concerning weight loss after surgical methods have been reported to range from 61% to 95% (Gloy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is known that substance use disorder is frequently associated with mental illnesses, especially with Bipolar Disorder and Schizophrenia, different prevalence rates are mentioned. [18] In the Epidemiologic Field Study of the American National Institute of Mental Health, it was reported that the prevalence of substance use disorder in individuals with schizophrenia spectrum disorder was 4.6%. [19] In many other studies, rates between 10% to 70% are mentioned.…”
Section: Discussionmentioning
confidence: 99%